RANCANG BANGUN APLIKASI BUDIDAYA PERIKANAN BERBASIS MOBILE “NUFARM” - Chatrine Sylvia; Fandi Halim; Thiofani Maureen Tjandra; Rizka Nurhudami (Politeknik Bisnis Indonesia, 2021)
The NUFARM application is a mobile application that delivers online aquaculture management services for aquaculture cultivators by providing information / news about aquaculture, cultivated organism’s growth monitoring by delivering real-time information about cultivation condition, and providing a marketplace for buying and selling transactions for business entrepreneurs or aquaculture cultivators. several problems have been found in the aquaculture industry which is comprise of the lack of reliable information sources on aquaculture management, the unavailability of media that able to assist farmers on accessing information about the place’s conditions and organisms that being cultivated, there is no place for buying and selling transactions specialized on aquaculture for farmers. entrepreneur in the aquaculture business sector. The application design provides various online aquaculture management services which are manifested in the several main features. NUMonitor which provides information about the condition of the organism in real-time (in the form of temperature, dissolved oxygen levels, and pH) for the user. NUFeed which able to feed organisms with variety of settings which is able to be scheduled, automatic feeding and manual feeding. NUPeep which is a camera sensor that able to display organism condition to the user visually. NULight as an additional feature with its function for adjusting the illumination level of for example the aquarium lights. NUShop that serves a place for trading transactions for cultivated organisms and their equipment. As well as the NUpdate feature that able to provide the latest information / news about aquaculture along with tips and tricks for aquaculture management. Keywords: aquaculture, aquaculture management, mobile applications